Pengaruh Penerapan Metode Storytelling dengan Menggunakan Media Flashcard dalam Meningkatkan Keterampilan Berbicara Siswa Kelas IV UPT SPF SD Negeri Mannuruki - Nurzyabina; Bahri, Aliem; Asnidar, Anin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the application of the storytelling method using flashcard media in improving the speaking skills of fourth-grade students of UPT SPF SD Negeri Mannuruki. This study uses quantitative experimental research (pre-experimental design) with a one-group pretest-posttest design experimental design. The sample used was 31 students of class IV B UPT SPF SD Negeri Mannuruki. Data collection techniques used were observation, testing and documentation. The data in this study were analyzed using descriptive and inferential statistical analysis methods. The results showed that there was an effect of the application of the storytelling method using flashcard media in improving the speaking skills of fourth-grade students of UPT SPF SD Negeri Mannuruki. This can be seen from the increase in test scores given before the storytelling method was applied using flashcard media which only obtained an average pre-test score of 56.6 and after treatment the average post-test score was 74.8. The calculation results with t-test analysis after tcount = 15.8 and ttable 2.024 then obtained tcount> ttable or 15.8> 2.042. So it can be concluded that H0 is rejected H1 is accepted. This means that the application of the storytelling method using flashcard media has an effect on the speaking skills of fourth grade students of UPT SPF SD Negeri Mannuruki.